2016
DOI: 10.1108/lodj-06-2014-0107
|View full text |Cite
|
Sign up to set email alerts
|

Diversity as an aspect of effective leadership: integrating and moving forward

Abstract: Purpose – The purpose of this paper is to elaborate an integrative framework that positions diversity considerations in a continuum of various leadership theories. The authors thus seek to differentiate between distinct leadership styles and assess their potential in fostering inclusive leader behaviors. Design/methodology/approach – The authors proceed to a brief review of the extant literature on diversity leadership by distinguishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 104 publications
2
33
0
Order By: Relevance
“…The current study empirically demonstrated that transformational leaders help foster an inclusive work environment wherein employees feel valued for their unique characteristics and that they belong as important members of the group. This extends previous theoretical frameworks that have suggested TFL as a possible leadership approach that may foster an inclusive climate (Gotsis & Grimani, ) by empirically examining TFL with perceptions of inclusion at both the department and work group levels. The leader's ability to inspire a shared vision of the future and create equitable employment practices has been conceptualized as key aspects of TFL and critical to fostering inclusion (Gotsis & Grimani, ; Guillaume et al, ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The current study empirically demonstrated that transformational leaders help foster an inclusive work environment wherein employees feel valued for their unique characteristics and that they belong as important members of the group. This extends previous theoretical frameworks that have suggested TFL as a possible leadership approach that may foster an inclusive climate (Gotsis & Grimani, ) by empirically examining TFL with perceptions of inclusion at both the department and work group levels. The leader's ability to inspire a shared vision of the future and create equitable employment practices has been conceptualized as key aspects of TFL and critical to fostering inclusion (Gotsis & Grimani, ; Guillaume et al, ).…”
Section: Discussionsupporting
confidence: 70%
“…This extends previous theoretical frameworks that have suggested TFL as a possible leadership approach that may foster an inclusive climate (Gotsis & Grimani, ) by empirically examining TFL with perceptions of inclusion at both the department and work group levels. The leader's ability to inspire a shared vision of the future and create equitable employment practices has been conceptualized as key aspects of TFL and critical to fostering inclusion (Gotsis & Grimani, ; Guillaume et al, ). More specifically, inclusive work‐related policies and practices are those that empower employees and promote the integration of differences (Guillaume et al, ).…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, the study of leadership antecedents is not often addressed (Barbuto & Wheeler, 2002;Hu, Wang, Liden, & Sun, 2012;Peus, Wesche, Streicher, Braun, & Frey, 2012;Sims, Gong, & Hughes, 2017). I argue that diversity intelligence is necessary for servant leadership to be realized, and advance that those leaders who execute greater diversity intelligence are more likely to behave and be perceived as servant leaders (Barbuto, Gottfredson, & Searle, 2014;Gotsis & Grimani, 2016;Hughes, 2016;van Dierendonck & Patterson, 2015).…”
mentioning
confidence: 99%
“…Leadership styles and governance structures also play crucial rules when managing inclusion within the diverse workforce. For example, Gotsis and Grimani [33] differentiate between distinct leadership styles and assess their potential in fostering inclusive leader behaviours and found four emerging leadership styles (ethical, authentic. servant and spiritual leadership) for informing inclusive climates within organisations.…”
Section: Although Pless and Maakmentioning
confidence: 99%